Subcutaneous Panniculitis-Like T-Cell Lymphoma in Two Pediatric Patients: An HIV-Positive Adolescent and a 4-Month-Old Infant. (1st June 2013) - Acree, Sara C.; Tovar, Jason P.; Pattengale, Paul K.; Wang, Larry L.; Church, Joseph A.; Gaynon, Paul S.; Cassarino, David S.
<x xml:space="preserve">Abstract</x> Subcutaneous Panniculitis-like T-cell lymphoma (SPTCL) is a rare subtype of childhood non-Hodgkin lymphoma. Subcutaneous Panniculitis-like T-cell lymphoma has an aggressive variant associated with the hemophagocytic syndrome (HPS). Patients without HPS show resolution of the disease with prednisone or immunosuppressive therapy unlike other T-cell lymphomas. One HIV-positive adolescent and one infant with multiple subcutaneous masses are presented and the literature is reviewed. Lesional cells were consistent with SPTCL alpha-beta type. Our cases, without HPS, showed complete resolution of their lesions when treated with non-aggressive therapies. Patients with SPTCL alpha-beta should be treated conservatively.